'Fervent spenglerians:' romanising the historic morphology of cultures in Spain (1922–1938). Issue 5 (4th July 2022) - Lemke Duque, Carl Antonius
ABSTRACT: This study analyses the impact of Oswald Spengler's (1880–1936) work in Spain during the interwar period. It proceeds with three steps as follows: The first part (II) investigates the reception of Spengler's historic morphology of cultures in the so-called circle of the Revista de Occidente . The second part (III) delves into the early echo of Spengler's work among the Spanish left up to the Second Spanish Republic. The third part (IV) focuses on the impact of Spengler's historic morphology among conservative traditionalists and members of the radical right prior to the Spanish Civil War. This analysis point towards broad, transideological debate on Spengler in Spain that the Spanish right then usurped and radicalised during the 1930s.